Field tests to measure trunk stability: Validity and reliability analysis - Juan Recio, C.; Barbado, D.; Lopez Plaza, D.; Garcia Vaquero, M. P.; Vera Garcia, F. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
INTRODUCTION: Although muscular fitness tests [e.g. Biering-Sorensen test (BST)], single leg stance balance tests [e.g. three plane core strength test (TPCST)] and lumbo-pelvic postural control tests [e.g. double-leg lowering test (DLLT)] are usually performed to assess trunk/core stability in field settings (Leetun et al., 2004; Weir et al., 2010), some doubts still exist about the validity and reliability of these measures (Sharrock et al., 2011; Weir et al., 2010). The aim of this study was to analyse the relationship between BST, TPCST and DLLT and gold standard tests to measure trunk stability, and to evaluate the reliability of these protocols. METHODS: 27 recreational male athletes participated in this study. Two protocols were used as gold standard tests to assess trunk stability: a) Trunk balance control test: a battery of static and dynamic tasks was performed to measure trunk balancing while sitting on stable and unstable seats placed on a force plate (Kistler 9286A). Postural and dynamic sway were assessed by analyzing the displacement of the centre of pressure; b) Sudden load test: quick and unexpected trunk loads in anterior, posterior and lateral directions were applied to the thorax by a pneumatic mechanism, while the participant was seated with the pelvis fixed. Trunk angular displacement was measured and the damping and stiffness coefficients of the trunk were calculated from the first 110 ms of data. One month after the gold standard measurements were carried out, the BST, TPCST and DLLT were performed in another recording session. Pearson and Sperman correlation coefficients were used to analyse the relationship between all variables. Each test was performed twice and the ICC was calculated to assess the reliability of the measures. RESULTS: Most variables showed good reliability (ICCs> 0.70), except for the damping coefficient in anterior loading direction and for all the variables of the TPCST (ICCs< 0.43). The DLLT was not sensitive enough to discriminate between most participants. No significant correlations were found between the BST score and the variables of the gold standard tests. Some significant correlations were found between the TPCST and several tasks of the trunk balance control test, but in such cases, the proportion of variance explained was low (17.38% < R2 < 37.33%). DISCUSSION: Although the 3 field tests have been widely used as trunk stability measures, our results question their reliability and validity and confirm the complexity of assessing trunk stability in field settings.